Thematic - Integrative Aqidah Teaching Material Model in the Independent Curriculum - Maryam Pakaya; Azizah Pakaya; Mowafg Abrahem Masuwd (ASSUNNAH PRESS, 2026)
The implementation of the Independent Curriculum requires the development of Islamic Religious Education teaching materials that are more flexible, contextual, and focused on strengthening students' character. In the context of Aqidah subjects, the main challenge lies in maintaining the depth of theological values while adapting them to thematic and integrative learning approaches. This research aims to develop a conceptual model for formulating thematic and integrative Aqidah teaching materials aligned with the Independent Curriculum. This study uses a qualitative approach, drawing on literature enriched by conceptual-analytical analysis of Islamic education literature, thematic learning, and Independent Curriculum policies. The results of the study show that the development of thematic and integrative Aqidah teaching materials should be based on the principles of integrating faith values with contextual themes, cross-disciplinary integration, student-centered learning, and orientation toward the formation of character and competencies in the 21st century. This research produced a conceptual model of Aqidah teaching materials that places Aqidah values as the core, a thematic-integrative approach as a framework for organizing materials, and contextual learning as an implementative orientation. As a form of operationalization of the model, this study also presents an illustration of the application of thematic and integrative Aqidah teaching materials. These findings are expected to make a theoretical and practical contribution to the development of relevant, adaptive, and meaningful Islamic Religious Education teaching materials in the context of the Independent Curriculum.